2018
DOI: 10.1007/s00414-018-1866-9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing details of stays abroad by sequential stable isotope analyses along human hair strands

Abstract: Multi-element stable isotope analyses of δC, δN, δS and δH values were performed along scalp hair strands to detect isotopic changes resulting from different stays abroad. One hair strand with a hair length of more than 50 cm originated from a German woman, who frequently made long-distance travels of 1 to 4 weeks. The second hair strand with a length of 15 cm was taken from a Japanese woman who went to Germany for a period of some months. Stable isotopic influences due to the stays abroad were clearly reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…However, the growth rate chosen in this study may not be suitable for other studies. We also added 0.8 cm to the distance of the hair segment to the hair root (Tables 2, 3) to make up the ∼0.5 cm of hair remaining at the scalp during cutting (LeBeau et al, 2011;Lehn et al, 2019) and ∼0.3 cm of hair residue left in the hair follicle (Jimenez et al, 2011). The "distance from hair root" is then used *"Distance from hair root" equals the "distance from cutting end" plus 0.8 cm, which accounts for the distance between the cutting end and the root (discussion in the section "Determining the age model of the observed isotopic profiles").…”
Section: Determining the Age Model Of The Observed Isotopic Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the growth rate chosen in this study may not be suitable for other studies. We also added 0.8 cm to the distance of the hair segment to the hair root (Tables 2, 3) to make up the ∼0.5 cm of hair remaining at the scalp during cutting (LeBeau et al, 2011;Lehn et al, 2019) and ∼0.3 cm of hair residue left in the hair follicle (Jimenez et al, 2011). The "distance from hair root" is then used *"Distance from hair root" equals the "distance from cutting end" plus 0.8 cm, which accounts for the distance between the cutting end and the root (discussion in the section "Determining the age model of the observed isotopic profiles").…”
Section: Determining the Age Model Of The Observed Isotopic Profilesmentioning
confidence: 99%
“…Interestingly, Lehn et al (2019) have found that the change of isotope signal on bundled hair profile is usually provoked by the fastest-growing hairs in the hair bundle because those fast-growing single hairs tend to be thicker and heavier thus their isotopic signals outweigh the others. Considering a commonly used mean hair growth rate of 1.1 cm/month and a proposed ± 30% intra-individual variability in single hair growth rate, they found that the growth rate of 1.4 cm per 30 days may be the best approach to calculate the exact dates of the isotopic shifts along the hair profile.…”
Section: Uncertainty Of Intra-individual Hair Growth Ratementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several studies have used the C, N and S isotope composition in human tissues (δ 13 C, δ 15 N, and δ 34 S) to investigate differences in human nutrition and dietary choices at the population scale [Reviewed in 3]. Keratinized tissues, hairs and nails, are an ideal substrate for analyzing δ 13 C, δ 15 N and δ 34 S values in dietary studies, as these elements are abundant in keratin and record dietary isotopic values chronologically as they grow [4][5][6][7]. Isotope data from hair can thus provide snapshots of the diet from an individual or population at a monthly temporal resolution [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%